The life cycle of cities. (February 2018) - Czamanski, Daniel; Broitman, Dani
Abstract: While an ever-growing percentage of the world's population is urban, the rate at which cities grow is not uniform. The lifetime of individual cities includes periods of fast growth, slow growth and periods of shrinkage. There exists an extensive literature concerned with possible means to manage specific pathologies. It is our view that the design of specific policies should be the result of a comprehensive model of urban health. While not all cities go through the entire life cycle, a comprehensive theory of cities and specific policies need to include specification of the interaction of the various forces that shape the entire range of urban patterns and identification of specific combinations of values that create phase transitions among these patterns. To sort these ideas we suggest that there is a need to consider and incorporate the structure and timing of innovation activities, agglomeration effects that they generate, interurban migration patterns and assorted feedback mechanisms. We hypothesize that these flows depend on the activity rhythms of the various processes and their differential impact on cities. We present a biology inspired rudimentary framework as a basis for the construction of an ABM of cities with a focus on the nature of time and as a basis for analyzing urban dynamics. 1